Comparison of Weighted Product Method and Simple Additive Weighting in Scholarship Recipient Selection: Comparison of Weighted Product Method and Simple Additive Weighting in Scholarship Recipient Selection - Oktaviani Oktaviani; Agung Triayudi; Ira Diana Solihati (Institute of Computer Science (IOCS), 2020)
SMA Dharma Karya as educational institutions annually held the scholarships are given to students based on criteria set by the school. However, in selecting the scholarship still use manual feared scholarships target. So the decision support system built in selecting scholarship learners using weighted product. In this study, using the method of weighted product and simple additive weighting as a comparison. From the results of research on the best methods of weighted product that is on the alternative perengkingan 14 with a total value of 0.0067401308233662 and the best perengkingan SAW method is also on the alternative 14 with a total value of 0.82. The results of a comparison test on the data obtained 263 product value weighted accuracy of 83.03% and a simple additive weighting of 60.45%. Results have the system usability percentage of 85.6% and has been tested BlackBox Addressing that the system can perform properly selecting scholarship recipients.